2013
DOI: 10.1016/j.jfineco.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

General equilibrium pricing of currency and currency options

Abstract: This paper presents a consumption-based general equilibrium model for valuing foreign exchange contingent claims. The model identifies a novel economic mechanism by exploiting highly but imperfectly shared consumption disaster with variable intensities which are the concerns to the representative investor under recursive utility. When applied to the data, the model simultaneously replicates i) the moderate option-implied volatilities; ii) substantial variations in the risk-neutral skewness of currency returns;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…evidence on the properties of variance and skewness risk in exchange rates (e.g., Carr and Wu, 2007a;Bakshi, Carr, and Wu, 2008;Du, 2013;Della Corte, Ramadorai, and Sarno, 2016;Londono and Zhou, 2016) and also relate our paper to recent work on crash risk in currency markets (see, e.g., Brunnermeier, Nagel, and Pedersen, 2008;Chernov, Graveline, and Zviadadze, 2016;Jurek, 2014;Farhi et al, 2015;Farhi and Gabaix, 2016;Daniel, Hodrick, and Lu, 2016). The link between sovereign risk, higher exchange rate moments, and currency crash risk suggested by our empirical results is also consistent with the literature on asset pricing implications of rare event risk for credit spreads and option prices, recently surveyed by Tsai and Wachter (2015).…”
Section: Motivation and Related Literaturementioning
confidence: 99%
“…evidence on the properties of variance and skewness risk in exchange rates (e.g., Carr and Wu, 2007a;Bakshi, Carr, and Wu, 2008;Du, 2013;Della Corte, Ramadorai, and Sarno, 2016;Londono and Zhou, 2016) and also relate our paper to recent work on crash risk in currency markets (see, e.g., Brunnermeier, Nagel, and Pedersen, 2008;Chernov, Graveline, and Zviadadze, 2016;Jurek, 2014;Farhi et al, 2015;Farhi and Gabaix, 2016;Daniel, Hodrick, and Lu, 2016). The link between sovereign risk, higher exchange rate moments, and currency crash risk suggested by our empirical results is also consistent with the literature on asset pricing implications of rare event risk for credit spreads and option prices, recently surveyed by Tsai and Wachter (2015).…”
Section: Motivation and Related Literaturementioning
confidence: 99%
“…The investors have arbitrage opportunities due to the different levels of jump intensities of money supplies in two countries.λ h =λ f tends to hold during a long time period empirically as in Ref. [12], so E[R s t ] tends to zero according to the above formula. The observation is consistent with the empirical results in Ref.…”
Section: The Modelmentioning
confidence: 99%
“…Their empirical results showed that the innovations to the two risk processes were not very correlated with each other, which was consistent with their model assumption that the diffusive volatility and jump intensity followed their own stochastic process. Instead of studying equilibrium stock options pricing in Santa-Clara and Yan [21], Du [12] studied equilibrium currency options pricing under recursive utility. In his consumption-based model, the consumptions in domestic and foreign countries were highly but imperfectly shared disaster with time-varying jump intensities.…”
Section: Introductionmentioning
confidence: 99%
“…Following the work of Du (2013), we use risk reversal to represent intermediary risk aversion. Risk reversal is regarded as a kind of insurance.…”
Section: Risk Aversion Channelmentioning
confidence: 99%
“…Consequently, intermediaries would require higher carry trade returns as compensation for bearing risk. To test our expectation, we first follow the work of Du (2013) in capturing risk aversion through so‐called risk reversal, which is the difference between the implied volatility of an out‐of‐the‐money call option and the implied volatility of an equally out‐of‐the‐money put. It measures the cost of buying protection on a currency position to limit possible gains and losses, since the price of risk reversal is positive (negative) if the risk‐neutral distribution of the exchange rate is positively (negatively) skewed.…”
Section: Introductionmentioning
confidence: 99%